A technique for multitarget tracking in synthetic aperture radar spotlight imaging mode based on promoted PHD filtering approach. Issue 2 (23rd February 2017) - Daryasafar, N.; Sadeghzadeh, R. A.; Naser‐Moghadasi, M.
Abstract: This paper investigates a new method based on promoted probability hypothesis density (PHD) filtering to simultaneously track several moving targets in data received by synthetic aperture radar (SAR) in spotlight imaging mode. Simultaneous tracking of several targets in the presence of high‐density clutters in environment, as the particular capability of the PHD filter, has turned it into a robust approach in SAR to track moving targets. Given the PHD filter function as a sequence of prediction and update steps, it is more reasonable to apply the approach to the data received by the SAR in spotlight imaging mode; however, according to the specified system parameters, such method is not impossible to be implemented using the Stripmap imaging mode. According to simulation results, applying Range Cell Migration Compensation to the raw data received by SAR before tracking operation results in high‐quality tracking of moving targets. Key Points: A new method based on promoted PHD filtering is proposed for tracking multiple moving targets simultaneously in the received data by SAR Implementation of RCMC onthe raw data received bySAR before the tracking operation, which results in high quality tracking of moving targets